Prospective Cohort Study of Remote Patient Monitoring with and without Care Coordination for Hypertension in Primary Care - Persell, Stephen D.; Petito, Lucia C.; Anthony, Lauren; Peprah, Yaw; Lee, Ji Young; Campanella, Tara; Campbell, Jill; Pigott, Kelly; Kadric, Jasmina; Duax, Charles J.; Li, Jim; Sato, Hironori (Applied Clinical Informatics, 2023)
Background Out-of-office blood pressure (BP) measurements contribute valuable information for guiding clinical management of hypertension. Measurements from home devices can be directly transmitted to patients' electronic health record for use in remote monitoring programs.Objective This study aimed to compare in primary care practice care coordinator-assisted implementation of remote patient monitoring (RPM) for hypertension to RPM implementation alone and to usual care.Methods This was a pragmatic observational cohort study. Patients aged 65 to 85 years with Medicare insurance from two populations were included: those with uncontrolled hypertension and a general hypertension group seeing primary care physicians (PCPs) within one health system. Exposures were clinic-level availability of RPM plus care coordination, RPM alone, or usual care. At two clinics (13 PCPs), nurse care coordinators with PCP approval offered RPM to patients with uncontrolled office BP and assisted with initiation. At two clinics (39 PCPs), RPM was at PCPs' discretion. Twenty clinics continued usual care. Main measures were controlling high BP (<140/90 mm Hg), last office systolic blood pressure (SBP), and proportion with antihypertensive medication intensification.Results Among the Medicare cohorts with uncontrolled hypertension, 16.7% (39/234) of patients from the care coordination clinics were prescribed RPM versus <1% (4/600) at noncare coordination sites. RPM-enrolled care coordination group patients had higher baseline SBP than the noncare coordination group (148.8 vs. 140.0 mm Hg). After 6 months, in the uncontrolled hypertension cohorts the prevalences of controlling high BP were 32.5% (RPM with care coordination), 30.7 % (RPM alone), and 27.1% (usual care); multivariable adjusted odds ratios (95% confidence interval) were 1.63 (1.12–2.39; p = 0.011) and 1.29 (0.98–1.69; p = 0.068) compared with usual care, respectively.Conclusion Care coordination facilitated RPM enrollment among poorly controlled hypertension patients and may improve hypertension control in primary care among Medicare patients.
Keywords: remote physiological monitoring; remote patient monitoring; primary care; hypertension; telemedicine